1996
DOI: 10.1016/0375-9601(96)00306-4
|View full text |Cite
|
Sign up to set email alerts
|

The origin of non-chaotic behavior in identically driven systems

Abstract: Recently it has been found that different physical systems driven by identical random noise behave exactly identical after a long time. It is also suggested that this is an outcome of finite precision in numerical experiments. Here we show that the origin of the non-chaotic behavior lies in the structural instability of the attractor of these systems which changes to a stable fixed point for strong enough drive. We see this to be true in all the systems studied in literature. Thus we affirm that in chaotic sys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 16 publications
(29 reference statements)
1
16
0
Order By: Relevance
“…Synchronization with λ < 0 occurs for σ 2 > 0.24. So, in contrast to the examples in [1][2][3][4][5][6][7][8], the sensitivity of this chaotic map can be suppressed by zero-mean noise, so that systems starting from different initial conditions will finally collapse into the same final orbit.The synchronization can be understood from the view point of the convergence region of the map. We perform two calculations: one is the distribution of the state of the system; and the other the distribution of the finite-time Lyapunov exponents defined as[5]…”
mentioning
confidence: 94%
“…Synchronization with λ < 0 occurs for σ 2 > 0.24. So, in contrast to the examples in [1][2][3][4][5][6][7][8], the sensitivity of this chaotic map can be suppressed by zero-mean noise, so that systems starting from different initial conditions will finally collapse into the same final orbit.The synchronization can be understood from the view point of the convergence region of the map. We perform two calculations: one is the distribution of the state of the system; and the other the distribution of the finite-time Lyapunov exponents defined as[5]…”
mentioning
confidence: 94%
“…Gade and Basu showed that this synchronization phenomena is indeed physical in certain cases, and for synchronization of those system the randomness is not vital [19]. Moreover we have shown that, in this kind of synchronization, the distribution of the random variable is vital and there exists on-off intermittency in the boundary of synchronization region [6].…”
Section: Introductionmentioning
confidence: 87%
“…One should notice that the random variable is multiplied commonly to every particles in the summation of Eq. (19), and this leads to on-off intermittency ofS n .…”
Section: A Uncoupled Map Lattice With Homogeneous Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the challenging problems is to understand the formation of structures, localized in both space and time, in turbulent fluid [15][16][17]. Recently lot of attention has been devoted to the role of fluctuations in onset, selection and evolution of such patterns and structures [18][19][20][21][22][23][24][25][26]. An interesting and counterintuitive observation is that the presence of noise can help sustain structures which otherwise would have been absent in an evolving dynamical system.…”
Section: Introductionmentioning
confidence: 99%